2018
DOI: 10.1108/bfj-11-2017-0626
|View full text |Cite
|
Sign up to set email alerts
|

Comparing German and Italian food banks

Abstract: For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This admittance can be a source of shame and embarrassment, thereby preventing people from visiting foodbanks (Caplan, 2016): a finding also observed in Dutch, German, and French contexts (Rombach, Bitsch, Kang, & Ricchieri, 2018;van der Horst, Pascucci, & Bol, 2014). Those who do visit often disclose that accessing aid has made them feel like 'failures' (Douglas, Sapko, Kiezebrink, & Kyle, 2015).…”
Section: Stigma Within Foodbank Helping Transactionsmentioning
confidence: 83%
“…This admittance can be a source of shame and embarrassment, thereby preventing people from visiting foodbanks (Caplan, 2016): a finding also observed in Dutch, German, and French contexts (Rombach, Bitsch, Kang, & Ricchieri, 2018;van der Horst, Pascucci, & Bol, 2014). Those who do visit often disclose that accessing aid has made them feel like 'failures' (Douglas, Sapko, Kiezebrink, & Kyle, 2015).…”
Section: Stigma Within Foodbank Helping Transactionsmentioning
confidence: 83%
“…: caterers, retailers, processors, farmers, food manufacturers and finally end-users) must perform his/ her role to prevent and mitigate food waste (Galli et al, 2019). Today, food banks have attracted the attention of numerous scholars across the length and breadth of most developed countries (See, Campbell et al, 2013;Booth and Whelan, 2014;Caplan, 2016;Rombach et al, 2018;Prayogo et al, 2018). Owing to food banking being an effective response to food insecurity (Enns et al, 2020).…”
Section: Food Banking In the Ashantimentioning
confidence: 99%
“…Many factors were identified to influence customer satisfaction when visiting food premises, including, food taste, service, price, environment and hygiene [ 3 , 4 ]. A study conducted by Fatimah and colleagues (2011) on Malaysian customers found that cleanliness was the main factor followed by food variety and location of the premises as criteria in selecting dining places [ 5 ].…”
Section: Introductionmentioning
confidence: 99%